Association of Education, Current Pregnancy Wanted, Total Children and Accompanied by Husband in Antenatal Care Visit with Antenatal Care Pregnant Women in Indonesia - Novi Susanti; Sri Ilawati; Putra Apriadi Siregar (LPPM STIKES KENDAL, 2022)
Antenatal care can be one way to reduce maternal and child mortality. Antenatal care is the initial screening for pregnant women to see the health condition of their babies and their babies; antenatal care is very important for pregnant women and their babies. This study aimed to analyze the relationship of education, current pregnancy wanted, total children and accompanied by husband in antenatal care visit with antenatal care pregnant women in Indonesia. This study uses secondary data from the 2017 IDHS on pregnant women. The number of samples in this study was 770 pregnant women. Data analysis in this study used bivariate analysis with chi-square test and Prevalent Rate (PR) with 95% CI. The results of this study indicate that the majority of pregnant women did not perform antenatal care in the incomplete category of 531 pregnant women (69%). There was no relationship between education and antenatal care for pregnant women (p=0. 771). There was a relationship between current pregnancy wanted (p<0. 001), total children (p<0. 001), accompanied by husband in Antenatal Care Visit (p<0. 001) and antenatal care for pregnant women in Indonesia. A pregnant woman whose husband does not accompany her in an antenatal care visit has a 29,268 times risk of having an incomplete antenatal care category compared to an incomplete category of antenatal care